1992
DOI: 10.1002/kin.550240706
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of oxidation of hydroxylamine by peroxomonosulphate

Abstract: The kinetics of the reaction (1) obey the rate law (2) in acetate buffered solutions. A comparison with HZOP and S Z O~' shows the reactivity order to be HPOZ < HS05-> SzO8'-. 0 1992

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…On the other hand, HA can directly react with oxidants such as H 2 O 2 , PMS, ozone (O 3 ), and periodate to generate reactive species . In 1992, the oxidation of HA by PMS was first reported, which focused on the reaction kinetics but the production of SO 4 •– and HO • was not confirmed . Recently, H 2 O 2 was reported to react with HA to generate HO • through one-electron transfer, confirmed by using electron paramagnetic resonance (EPR) analysis and benzoic acid as a HO • probe .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, HA can directly react with oxidants such as H 2 O 2 , PMS, ozone (O 3 ), and periodate to generate reactive species . In 1992, the oxidation of HA by PMS was first reported, which focused on the reaction kinetics but the production of SO 4 •– and HO • was not confirmed . Recently, H 2 O 2 was reported to react with HA to generate HO • through one-electron transfer, confirmed by using electron paramagnetic resonance (EPR) analysis and benzoic acid as a HO • probe .…”
Section: Introductionmentioning
confidence: 99%
“…•− and HO • was not confirmed. 17 Recently, H 2 O 2 was reported to react with HA to generate HO • through one-electron transfer, confirmed by using electron paramagnetic resonance (EPR) analysis and benzoic acid as a HO • probe. 18 The reaction mechanisms involve two-steps: H 2 O 2 initially reacts with protonated HA to generate HO • and NH 3 O •+ , and NH 3 O •+ further reacts with H 2 O 2 to generate HO • .…”
Section: Introductionmentioning
confidence: 99%
“…Peroxomonosulfate is a potential oxidant, and a large number of kinetic studies by peroxomonosulfate are reported in acidic and alkaline media [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The kinetics of oxidation of unsaturated alcohols such as crotyl alcohol (CrA) by sodium bis[-2-ethyl-2hydroxybutanato(2-)] oxochromate(V) [19] has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Peroxomonosulfate ion (HSO 5 – ), the anion of Caro’s acid (H 2 SO 5 ), is an inexpensive and environmentally friendly oxidant and has wide applications. Oxidation studies of peroxomonosulfate (PMS) with several compounds such as hypophosphorous acid, indole-3-acetic acid, oxovanadium­(IV) and its aminopolycarboxylate, aromatic aldehydes, alkyl thiocyanates, tris­(1,10-phenanthroline)­iron­(II), hydroxylamine, ascorbic acid, nickel­(II) lactate, vanillin, and amino acids, , have been reported.…”
Section: Introductionmentioning
confidence: 99%